AB0368 Systematic review of efficacy and safety of biological therapies in lupus nephritis. (23rd January 2014) - Salgado, E.; Rosario, M. P.; Loza Santamaría, E.
Abstract : Objectives: The aim of this study is to analyze the efficacy and safety of 10 biological therapies (BT) for lupus nephritis. These therapies are infliximab (IFX), etanercerpt (ETN), adalimumab (ADA), golimumab (GOL), certolizumab (CTZ), abatacept (ABA), rituximab (RTX), anakinra (ANK), tocilizumab (TCZ) and belimumab (BLM). Methods: A systematic review was undertaken searching on Medline, Embase and Cochrane Central. As well as abstracts from EULAR and ACR meetings were included. Citations from all selected articles were also reviewed. We identified studies with or without comparatoron adult patients with Systemic Lupus Erythematous (SLE) with active lupus nephritis, who had received BT. All results that could be considered as efficacy outcomes and all reported adverse events (AE) were collected. Patient characteristics, treatments and study design were recorded. Meta-analyses, systematic reviews, clinical trials (CT) and observational studies were included as well as all case series which involved at least 5 patients. Level of evidence was evaluated with CEBM Levels of Evidence 1 scale. Results: After selection by title and abstract and full reading of the text, a total of 22 publications that involved 20 studies were included. The search did not find any publications that meet inclusion criteria for ETN, ADA, GOL, CTZ, ANK or TCZ. Regarding to IFX, only two studies with nine patients each were found. Decrease in proteinuria ≥50 % was observed in 11 of the 18 patients from these two publications. Two of 18 patients presented infusion reactions. Regarding to ABA, two analysis with different definition of complete renal response (CRR) from the same phase 2/3 randomized, double-blind, placebo-controlled, CT were selected (1, 2 ). Both analyses found a higher effect of ABA compared to placebo on the decrease in proteinuria in the subgroup of patients that presented nephrotic syndrome at baseline. Herpes zoster was more frequent in ABA treated patients. Regarding to RTX, 15 studies in lupus nephritis were selected. Six of them, studied the combination therapy RTX+ CYC. A phase 3, randomized, double-blind, CT without pure membranous nephritis and with all patients on background mycophenolate mofetil (MMF) showed that RTX is not superior to achieve a CRR, although a benefit was seen in other secondary outcomes (3 ). Combination therapy of RTX + CYC did not provide an extra benefit. RTX treated patients had not increased infections or cancer. Regarding to BLM, two analyses of renal parameters in patients from lupus CT which had not been designed for renal outcomes were selected (4, 5 ). They showed that BLM could have a benefit in renal outcomes. Combination therapy of BLM+ MMF provided an extra benefit in renal parameter of SELENA-SLEDAI. Safety data of this subgroup of patients were not provided. Conclusions: Although some data suggest possible benefits of ABA and BLM, results from CT are inconclusive because the heterogeneity of definition in renal response and the absence of designs with renal primary outcomes. References: Arthritis Rheum 2011, 63(Suppl 10):2469. Arthritis Rheum 2011, 63(Suppl 10):2474. Arthritis Rheum 2012, 64(4):1215-1226. Arthritis Rheum 2011, 63(Suppl 10):2472. Ann Rheum Dis 2012, 71(Suppl3):536. Disclosure of Interest: None Declared